Automation of the College of Science Library its effects on the functional organization - Bugarin, Marijane E. (1997)
This study was conducted to find out the effects of automation on the functional organization of the College of Science Library. The results indicate a positive effect on the advancements brought about by the automation, on the functional organization of the CS library. In the initial stages, there was an increase in the number of employees in all levels of the functional organization, except for the managerial level. Eighty percent of the respondents indicated a change in the director's decision-making responsibilities. There were also indications of a decentralization in the decision-making. There was a sixty percent implication that there was indeed an increase in the frequency of communication within the functional organization. Communication also proved to be an important factor in the effective coordination of personnel. It also played a major role in the success of the automation process. The automation of the CS library eliminated some jobs in the lower levels but no one was laid off as a result of this. Those whose jobs were ostracized are now working with modified tasks.